The Effect of Green Branding, Relational Marketing, and Product Innovation on Perceived Customer Value in the West Java Tourism Industry - Sudirjo, Frans; Yoga, Tirta; Mujib, Haqibul (West Science Interdisciplinary Studies, 2024)
This study examines the impact of Green Branding, Relational Marketing, and Product Innovation on Perceived Customer Value in the context of the West Java tourism industry. A quantitative approach using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was employed to analyze data collected from tourists visiting various destinations in West Java. The results indicate that Green Branding, Relational Marketing, and Product Innovation significantly influence tourists' perceptions of value. Specifically, Green Branding initiatives emphasizing environmental sustainability, relational strategies enhancing customer interactions, and innovative tourism products contribute positively to tourists' perceived value. These findings underscore the strategic importance of sustainability practices, customer relationship management, and continuous innovation in enhancing overall tourist satisfaction and loyalty in West Java. Practical implications for tourism stakeholders and directions for future research are discussed.